Explanatory language in dental informed consent communication - Pysarenko, Anastasiia; Kostenko, Viktoriia (The Ukrainian Scientific Medical Youth Journal, 2025)
Informed consent is a legal and ethical cornerstone of dental care, yet its effectiveness depends not only on content but also on clarity of communication. While existing research extensively covers the ethical and legal aspects, less attention has been given to the linguistic strategies that shape patient comprehension. This study examines the use of code glosses, i.e. in-text clarifications of technical terms, in 50 informed consent forms (ICFs) used in U.S. dental practices. Using Hyland’s metadiscourse model and the Text Inspector tool, glosses were identified, categorized, and analyzed across different sections of the forms. Results show that Explanation glosses dominate (45.9%), with Implication and Exemplification glosses each at 19.7%. Most glosses appear in Procedure (30%) and Diagnosis (28%) sections, while fewer are found in Risk (22%) and Consent statements (10%). These findings highlight areas where patients may receive insufficient support to understand complex or abstract information, particularly when it comes to making truly informed choices. Glosses improve readability by unpacking specialized language and reducing cognitive load, especially under conditions of stress or limited health literacy. Despite their benefits, certain gloss types, such as analogies or conditionally phrased advisories, remain underused, possibly due to legal caution or a preference for standardized phrasing. The study underscores that code glosses are essential communicative tools, not mere stylistic additions. Greater integration of patient-friendly language and multimodal strategies is recommended to strengthen informed consent practices and promote clearer, more equitable healthcare communication.